Expression of the Acidothermus cellulolyticus E1 endoglucanase in Caldicellulosiruptor bescii enhances its ability to deconstruct crystalline cellulose - Chung, Daehwan (Biotechnol Biofuels, 2015)
BACKGROUND: The Caldicellulosiruptor bescii genome encodes a potent set of carbohydrate-active enzymes (CAZymes), found primarily as multi-domain enzymes that exhibit high cellulolytic and hemicellulolytic activity on and allow utilization of a broad range of substrates, including plant biomass without conventional pretreatment. CelA, the most abundant cellulase in the C. bescii secretome, uniquely combines a GH9 endoglucanase and a GH48 exoglucanase in one protein. The most effective commercial enzyme cocktails used in vitro to pretreat biomass are derived from fungal cellulases (cellobiohydrolases, endoglucanases and a β-d-glucosidases) that act synergistically to release sugars for microbial conversion. The C. bescii genome contains six GH5 domains in five different open reading frames. Four exist in multi-domain proteins and two as single catalytic domains. E1 is a GH5 endoglucanase reported to have high specific activity and simple architecture and is active at the growth temperature of C. bescii. E1 is an endo-1,4-β-glucanase linked to a family 2 carbohydrate-binding module shown to bind primarily to cellulosic substrates. We tested if the addition of this protein to the C. bescii secretome would improve its cellulolytic activity. RESULTS: In vitro analysis of E1 and CelA shows synergistic interaction. The E1 gene from Acidothermus cellulolyticus was cloned and expressed in C. bescii under the transcriptional control of the C. bescii S-layer promoter, and secretion was directed by the addition of the C. bescii CelA signal peptide sequence. The vector was integrated into the C. bescii chromosome at a site previously showing no detectable detrimental consequence. Increased activity of the secretome of the strain containing E1 was observed on both carboxymethylcellulose (CMC) and Avicel. Activity against CMC increased on average 10.8 % at 65 °C and 12.6 % at 75 °C. Activity against Avicel increased on average 17.5 % at 65 °C and 16.4 % at 75 °C. CONCLUSIONS: Expression and secretion of E1 in C. bescii enhanced the cellulolytic ability of its secretome. These data agree with in vitro evidence that E1 acts synergistically with CelA to digest cellulose and offer the possibility of engineering additional enzymes for improved biomass deconstruction with the knowledge that C. bescii can express a gene from Acidothermus, and perhaps other heterologous genes, effectively. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13068-015-0296-x) contains supplementary material, which is available to authorized users.